2021
DOI: 10.1016/j.crad.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related intracranial imaging findings: a large single-centre experience

Abstract: Aim To describe the neuroradiological changes in patients with coronavirus disease 2019 (COVID-19). Materials and methods A retrospective review was undertaken of 3,403 patients who were confirmed positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and admitted to our institution between 1 March 2020 and 31 May 2020, and who underwent neuroimaging. Abnormal brain imaging was evaluated in detail and various imaging patterns on magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 23 publications
5
50
1
1
Order By: Relevance
“…All 18 studies were included in the meta-analysis to calculate the global prevalence of hemorrhagic stroke in COVID-19 patients and the frequency of symptoms leading to hospital admission 32 49 . Data from nine studies were included to calculate the mortality rate of hemorrhagic stroke in COVID-19 patients 32 , 33 , 35 37 , 40 , 45 , 48 , 49 , while the other nine studies did not report relevant data. The 18 studies and the prevalence of hemorrhagic stroke reported in each of them are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All 18 studies were included in the meta-analysis to calculate the global prevalence of hemorrhagic stroke in COVID-19 patients and the frequency of symptoms leading to hospital admission 32 49 . Data from nine studies were included to calculate the mortality rate of hemorrhagic stroke in COVID-19 patients 32 , 33 , 35 37 , 40 , 45 , 48 , 49 , while the other nine studies did not report relevant data. The 18 studies and the prevalence of hemorrhagic stroke reported in each of them are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Delirium is an acute impairment of consciousness that affects all higher cerebral-cortical functions and is common in seriously medically ill patients, with reported incidence rates between 4% and 55% among patients in intensive care units (ICUs) (1). Increasingly recognized as commonly occurring during the COVID-19 pandemic (2), delirium has a higher prevalence than other conditions affecting the central nervous system (CNS) when compared with stroke, encephalitis, convulsions, or meningitis (3).…”
mentioning
confidence: 99%
“…There are limited reports on delirium during the COVID-19 pandemic, mostly case reports (11)(12)(13) or retrospective studies (3,14), although one prospective study of two ICU cohorts in France reported a 79.5% incidence rate of delirium using the Confusion Assessment Method-ICU (CAM-ICU) (9). COVID-19 delirium often presents as the hyperactive motor subtype in up to 69% of patients (9,12), although the hypoactive subtype may be more common in the elderly (11,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We are grateful to Dr. Kawada for highlighting additional cases of non-aneurysmal subarachnoid haemorrhage (SAH) which have occurred in the context of severe coronavirus disease 2019 (COVID-19). Indeed, several additional case series have recently been published, including those with pathological findings [ 1 – 3 ], and we anticipate that additional cases of CNS haemorrhagic complications of COVID-19 infection will be reported in emerging registry data.…”
mentioning
confidence: 99%